Cutting the Mustard: New Insights Into the Plant Economy of Late Neolithic Tepe Khaleseh (Iran). Issue 2 (2nd July 2020) - Whitlam, Jade; Valipour, Hamid Reza; Charles, Michael
ABSTRACT: Excavations at Tepe Khaleseh, a small-settlement mound in the Zanjan Province of northwest Iran, have uncovered numerous structures dating to the second half of the sixth millennium B.C., including a pottery kiln. The charred plant remains recovered from the site provide evidence for the cultivation of a diverse spectrum of cereals, along with pulses, which are rare at contemporary sites in the region. Analysis of the archaeobotanical assemblage has also permitted a reconstruction of fuel use at the site, with wild mustards identified as having played a key role in the settlement's fuel economy. The results presented here expand significantly on our understanding of plant management in northern Iran during the Late Neolithic, a period when we see the spread of farming out of the Fertile Crescent and into Eurasia.